Inisiasi Menyusu Dini (IMD) Berpengaruh Terhadap Kelancaran ASI Pada Ibu Bersalin Sectio Cesarea - Efa Suzana; Yanti Sutriyanti; Farida Esmianti Esmianti (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
The success of breastfeeding is determined in the first 24 hours after the mother gives birth. In the first hours after giving birth, the hormone oxytocin is released which is responsible for the production of breast milk, namely through Early Initiation of Breastfeeding (IMD). IMD is generally only applied to mothers with normal deliveries, so this study aims to analyze the effect of IMD on the smoothness of breastfeeding in mothers who gave birth by caesarean section. This study uses a quasi-experimental design with a posttest only with control group design. The study population was all mothers who gave birth by cesarean section at the Curup Hospital, Kab. Rejang Lebong Bengkulu Province for 24 days was carried out from December 08, 2020 to December 31, 2020. Sampling was carried out purposively with a total of 20 people in the intervention group and 20 people in the control group. In the intervention group, IMD was given for one hour, while the control group was not given IMD. The statistical test used is the dependent t-test. The results of the analysis showed that there were significant differences in the parameters of smooth breastfeeding, namely the frequency of feeding, the frequency of urination, the frequency of defecation, the squeeze of breast milk, and the feeling of tension in the breasts, in the intervention group and the control group (p-value <0.001). This shows that there is an effect of IMD on the smoothness of breastfeeding in mothers giving birth by cesarean section. IMD can stimulate the secretion of the hormone prolactin which is in charge of producing breast milk, and the hormone oxytocin for the release of breast milk, causing smooth milk production. The implementation of IMD can be included in hospital service standards not only for mothers with normal deliveries, but also for mothers with cesarean delivery. Keywords: Early Initiation of Breastfeeding, Smooth Breast Milk, Sectio Cesarea